Activatable Multiplexed 19F Magnetic Resonance Imaging Visualizes Reactive Oxygen and Nitrogen Species in Drug-Induced Acute Kidney Injury - Li, Ao; Luo, Xiangjie; Li, Lingxuan; Chen, Dongxia; Liu, Xing; Yang, Zhaoxuan; Yang, Lijiao; Gao, Jinhao; Lin, Hongyu (Analytical chemistry (Washington), 2021)
In vivo levels of reactive oxygen species (ROS) and reactive nitrogen species (RNS) are critical to many physiological and pathological processes. Because of the distinct differences in their biological generation and effects, simultaneously visualizing both of them could help deepen our insights into the mechanistic details of these processes. However, real-time and deep-tissue imaging and differentiation of ROS- and RNS-related molecular events in living subjects still remain a challenge. Here, we report the development of two activatable 19F magnetic resonance imaging (MRI) molecular probes with different 19F chemical shifts and specific responsive behaviors for simultaneous in vivo detection and deep-tissue imaging of O2 •– and ONOO–. These probes are capable of real-time visualization and differentiation of O2 •– and ONOO– in living mice with drug-induced acute kidney injury by interference-free multiplexed hot-spot 19F MRI, illustrating the potential of this technique for background-free real-time imaging of diverse biological processes, accurate diagnosis of various diseases in deep tissues, and rapid toxicity evaluation of assorted drugs.